Special-Analysis of Administrative Services in City of Mosul Applied Study (College of Basic Education Research Journal, 2025)
Administrative factor is considered one of the most important factors of emergence and development of human settlements. These services usually include administrative units of government, administration, and municipality institutions, with many services of administrative dimension, such as security and defense services, courts, police and civil defense departments, social insurance services,  financial and banking services.In  city of Mosul, there are 30 service institutions with an area of 49,604 m2, or 0.2% of total area of Mosul, which is 222,000,000 m2. Number of workers in these services reached 15,339 individuals, constituting 0.6 of  total population of the city , which was 2,058,404 people in 2012. These institutions are in downtown district of  Mosul, in addition to  surrounding areas.
Keywords: services; administration services; spatial analysis; Mosul city